The Essence Of "Acmeological Approach". - Batiraliyev Maftunaxon Batirali qizi (Euro Asian Journal Publishing, 2024)
Pedagogical and psychological activities aimed at shaping, developing, and socializing an individual are organized based on specific approaches. In modern pedagogy, the processes of educating, teaching, and developing individuals are carried out in accordance with dozens of approaches. For instance, creative, innovative, interactive, vitagenic, competence-based, axiological, and acmeological approaches play a distinctive role in personal development. However, in the context of global informatization, marginal (intermediate, mixed) culturalization, and the growing emphasis on individual egocentrism, the application of an acmeological approach in pedagogical processes becomes increasingly relevant. Moreover, the acmeological approach, implemented in line with the principle of "individual to perfect human being," holds particular significance in ensuring an individual’s achievement of excellence and harmony in social, physical, intellectual, emotional, creative, and professional development. The article examines the essence of the acmeological approach based on analysis.
Keywords: individual; acmeology; perfection